Рябиновый клин - Рубина Дина Ильинична (Большая проза Дины Рубиной, 2021)
Экземпляры: ф14 (20220726) / Инвентарный номер: 63419 / Цена: / Сис.шифр: Р2 / Авт.знак: Р 82 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6